Media Informasi Peraga Alat Fitness Berbasis Multimedia - Rosmiati Rosmiati; Bayu Pratama Nugroho; Susi Hendartie; Sulistyowati Sulistyowati; Rudini Rudini (Jurnal Sains Komputer dan Teknologi Informasi, 2022)
Fitness sports is one of the most popular sports by today's society, even fitness has become a people's lifestyle. But not everyone can make fitness a healthy lifestyle due to limited knowledge and knowledge about the world of fitness itself. This has been anticipated by providers of fitness sports venues. By providing the services of several trainers who help customers in running fitness properly and correctly. However, to be able to use the services of a Personal Trainer provided by the place provider requires a large amount of money. Another obstacle when doing fitness activities is the lack of understanding of good and correct fitness movements so that participants make the wrong movements during exercise so that they are not healthy and the ideal body is obtained but muscle injury due to incorrect fitness training patterns that are applied, this is because some customers do not use the services of a Personal Trainer. The problem of this research is how to design and manufacture a software in the form of multimedia-based information media for fitness equipment, which can provide information about usability, images, animations, and video demonstrations of fitness equipment. The purpose of making this program is as a media demonstration of how to use fitness equipment properly and correctly to help fitness customers use Macromedia Flash. The final result of this research is the application of multimedia-based fitness equipment demonstration media information as a fitness equipment demonstration media that can be used by fitness instructors or customers for fitness activities